From STEM to STEAM: An Enactive and Ecological Continuum - Videla, Ronnie; Aguayo, Claudio; Veloz, Tomas (Frontiers in Education, 2021)
STEM and STEAM education promotes the integration between science, technology, engineering, mathematics and the arts. The latter aims at favoring deep and collaborative learning on students, through curricular integration in K-12 science education. The enactive and ecological psychology approach to education puts attention on the role of the teacher, learning context and socio-cultural environment in shaping lived learning experiences. The approach describes education as a a process of embodied cognitive assemblage of guided perception and action.The latter process is depends on the interaction of learners with digital and/or analogue learning affordances existing within the socio-technological environment. This paper proposes that the scope of an enactive-ecological approach can be extended to the domain of learning science, technology, engineering, arts and mathematics (STEAM), especially when it comes to understanding deep roots of the learning process. We first present an exhaustive literature review regarding the foundations of both the enactive and the ecological learning theories, along with their differences and key similarities. We then describe the fundamentals and latest research advances of an integrated STEAM pedagogy, followed by the notion of mixed reality (XR) as an emerging educational technology approach, offering an understanding of its current foundations and general disposition on how to understand digital immersion from ecological psychology. Next, we propose a systems theoretical approach to integrate the enactive-ecological approach in STEAM pedagogy, framed in the Santiago school of cognition attending to the interactive dynamics occurring between learners and their interaction with learning affordances existing within their educational medium, establishing that sensorimotor contingencies and attentional anchors are important to restrict sensory variety and stabilize learning concepts. Finally, we consider two empirical studies, one from Chile and the other from New Zealand, in which we demonstrate how the enactive-ecological approach build upon a systems theory perspective can contribute to understanding the roots of STEAM learning and inform its learning design.